2016
DOI: 10.3390/polym8080311
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-Enzymatic Synthesis of Perfluoroalkyl-Functionalized Dendronized Polymers as Cyto-Compatible Nanocarriers for Drug Delivery Applications

Abstract: Among amphiphilic polymers with diverse skeletons, fluorinated architectures have attracted significant attention due to their unique property of segregation and self-assembly into discrete supramolecular entities. Herein, we have synthesized amphiphilic copolymers by grafting hydrophobic alkyl/perfluoroalkyl chains and hydrophilic polyglycerol [G2.0] dendrons onto a co-polymer scaffold, which itself was prepared by enzymatic polymerization of poly[ethylene glycol bis(carboxymethyl) ether]diethylester and 2-az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…It has been observed that the formulation of curcumin/amphiphile in 1 : 5 ratio (w/w) led the C-18 alkyl containing amphiphile 22 to encapsulate higher percentage of curcumin as compared to the C-18 alkyl functionalized PEGylated copolymers employing 1 : 2 curcumin/polymer ratio (Table 4). 48 Moreover, the synthesized amphiphiles 20-22 using 1 : 5 and 1 : 2 formulation ratio were found to possess superior transport efficiency, transport capacity and % encapsulation efficiency as compared to the alkyl and peruoroalkyl-functionalized dendronized polymers synthesized earlier by our group, 58 wherein 1 : 3 curcumin/polymer ratio was used (Table 4). Furthermore, Rabanel et al 59 also used 1 : 5 loading ratio for PEGpoly lactic acid (PLA) polymers (PEG 8%-g-PLA, PEG 20%-g-PLA, PEG-b-PLA and OH-g-PLA) but reported lower % transport and encapsulation efficiency than our system, with the exception of PEG 8%-g-PLA (Table 4).…”
Section: Encapsulation Potentialmentioning
confidence: 86%
See 2 more Smart Citations
“…It has been observed that the formulation of curcumin/amphiphile in 1 : 5 ratio (w/w) led the C-18 alkyl containing amphiphile 22 to encapsulate higher percentage of curcumin as compared to the C-18 alkyl functionalized PEGylated copolymers employing 1 : 2 curcumin/polymer ratio (Table 4). 48 Moreover, the synthesized amphiphiles 20-22 using 1 : 5 and 1 : 2 formulation ratio were found to possess superior transport efficiency, transport capacity and % encapsulation efficiency as compared to the alkyl and peruoroalkyl-functionalized dendronized polymers synthesized earlier by our group, 58 wherein 1 : 3 curcumin/polymer ratio was used (Table 4). Furthermore, Rabanel et al 59 also used 1 : 5 loading ratio for PEGpoly lactic acid (PLA) polymers (PEG 8%-g-PLA, PEG 20%-g-PLA, PEG-b-PLA and OH-g-PLA) but reported lower % transport and encapsulation efficiency than our system, with the exception of PEG 8%-g-PLA (Table 4).…”
Section: Encapsulation Potentialmentioning
confidence: 86%
“…6). This 48 1 : 2 --15.41 Stearoyl polymer 48 1 : 2 --9.26 50% peruoroalkyl-functionalized dendronized polymers 58 1 : 3 0.53 213.17 1.6 70% peruoroalkyl-functionalized dendronized polymers 58 1 : 3 0.45 176.75 1.4 50% alkyl-functionalized dendronized polymers 58 1 : 3 0.27 98.95 0.8 70% alkyl-functionalized dendronized polymers 58 1 : 3 0.39 135.41 1.2 PEG-PLA polymer 59 1 : 5 <2 -</¼ 10 PEG 8%-g-PLA polymer 59 1 : 5 5 -15 mPEG 2000 -OA polymer 60 1 : 5 $6 -$20…”
Section: Encapsulation Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…As a part of our ongoing research program to synthesize a wide variety of amphiphilic nanocarrier systems capable of forming different morphological aggregates because of varied hydrophilic and hydrophobic segments, herein, we have used triglycerol, an oligomer of glycerol, as a backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Host-guest adsorption exploits characteristic morphological properties of substrates to separate and adsorb only the substrates which can fit into the macrocyclic cavities. This phenomenon was adopted from biological macrocyclic chelators [13,14] and supramolecular chemistry [15][16][17]. Attempts to translate this mechanism onto adsorbents have not been very successful, with few exceptions (e.g., the SuperLig ® adsorbent) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%